Incidental Neurofibroma on 18F-Fluorocholine PET/MR. (September 2015) - Agrawal, Kanhaiyalal; Sajjan, Rakesh S.; Gavra, Maria; Fraioli, Francesco; Bomanji, Jamshed; Syed, Rizwan
Abstract : Abstract: Neurofibromas are benign peripheral nerve sheath tumors. We described a unique case of recurrent prostate cancer with coexisting neurofibroma diagnosed on 18 F-fluorocholine PET/MRI.